Analysis of Factors Causing Students’ Low Creative Thinking Abilities in Learning Mathematics: A Literature Review - Yatri, Alya Eka; Mulbar, Usman (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2026)
This study aims to analyze and identify various previous research findings regarding factors contributing to students’ low creative thinking skills. This study used a literature review method with a qualitative descriptive approach. Data were obtained from 13 previous research journals published between 2019 and 2025. The results of the study indicate that there are four main factors that play a role: cognitive, affective or psychological, environmental, and instructional factors. Cognitive factors include a lack of divergent thinking skills, flexibility, and understanding of mathematical concepts. Affective and psychological factors include low intrinsic motivation, self-efficacy, self-confidence, and high levels of math anxiety that hinder students’ courage to think openly and try new ideas. Environmental factors include a lack of support from teachers and peers, as well as a learning environment that does not encourage freedom of expression. Instructional factors are related to the application of learning methods that are still conventional and do not challenge students’ creative thinking skills. These findings confirm that improving mathematical creative thinking skills requires a holistic approach through strengthening student motivation and self-confidence, creating a supportive learning environment, and implementing innovative learning strategies oriented towards the creative thinking process.